Direct, enantioselective α-alkylation of aldehydes using simple olefins - Capacci, Andrew G. (Nat Chem, 2017)
Although the α-alkylation of ketones has already been established, the analogous reaction using aldehyde substrates has proven surprisingly elusive. Despite the structural similarities between the two classes of compounds, the sensitivity and unique reactivity of the aldehyde functionality has typically required activated substrates or specialized additives. Here, we show that the synergistic merger of three catalytic processes—photoredox, enamine and hydrogen-atom transfer (HAT) catalysis—enables an enantioselective α-aldehyde alkylation reaction that employs simple olefins as coupling partners. Chiral imidazolidinones or prolinols, in combination with a thiophenol, iridium photoredox catalyst and visible light, have been successfully used in a triple catalytic process that is temporally sequenced to deliver a new hydrogen and electron-borrowing mechanism. This multicatalytic process enables both intra- and intermolecular aldehyde α-methylene coupling with olefins to construct both cyclic and acyclic products, respectively. With respect to atom and step-economy ideals, this stereoselective process allows the production of high-value molecules from feedstock chemicals in one step while consuming only photons.